Digital document processing : (Springer, 2007)
The book address the major and frontier topics in the field of document analysis are brought together into a single volume creating a unique reference source. The book focus on Document structure analysis followed by OCR of Japanese, Tibetan and Indian printed scripts.Online and offline handwritten text recognition approaches; Japanese postal and Arabic check processing; Document image quality modelling, mathematical expression recognition, graphics recognition, document information retrieval, super resolution text, metadata extraction in digital library;Biometric and forensic aspects: individuality of handwriting detection; Web document analysis, text and hypertext mining and bank check data mining